Examining theses and dissertations: Demystifying the process - Govender, Krihshna Kistan (South African Journal of Higher Education, 2016)
Since the examinations process is sometimes ‘enshrouded in mystery’ this paper adds to the postgraduate examination culture by reporting the results of an exploratory study conducted in two phases in the Faculty of Management Studies at a large research university in South Africa. Following an in-depth review of the examiners’ reports for a three-year period (2009-2011), an electronic survey was conducted among the examiners of a business faculty at a large research university, who were appointed during the aforementioned period. It became evident from this study that although there are variations in terms of the range of requirements, universally examiners of PhDs strive to achieve the same objectives, namely that the candidate should undertake a substantial and coherent original piece of research worthy of publication. When developing their reports of theses and dissertations, the following themes emerged: literature, technical presentation, content, methodology, which themes are also more less similar to other international findings. Furthermore, the examiners perception of a good/poor/passable thesis/dissertation stems from or is linked to the ‘unpacking’ the abovementioned themes. There is also much congruence between the comments in the examiners’ reports, and what they reported in the survey. The findings albeit exploratory, can be useful to research supervisors, examiners, and postgraduate (PG) research students.